Govindjee, an institution, at his 80th (really 81st) birthday in Třeboň in October, 2013: a pictorial essay - Prášil, Ondřej (Photosynthesis research, 2014)
Govindjee (one name only), who himself is an institution, has been recognized and honored by many in the past for he is a true ambassador of "Photosynthesis Research" to the World. He has been called "Mr. Photosynthesis", and compared to the Great Wall of China. To us in Třeboň, he has been a great research collaborator in our understanding of chlorophyll a fluorescence in algae and in cyanobacteria, and more than that a friend of the Czech "Photosynthesis" group, from the time of Ivan Šetlík (1928-2009) and of Zdeněk Šesták (1932-2008). Govindjee's 80th (really 81st) birthday was celebrated by the Institute of Microbiology, Laboratory of Photosynthesis, by toasting him with an appropriate drink of a suspension of green algae grown at the institute itself. After my presentation, on October 23, 2013, of Govindjee's contributions to photosynthesis, and his intimate association with the photosynthetikers (in Jack Myers's words) of the Czech Republic, Govindjee gave us his story of how he began research in photosynthesis in the late 1950s. This was followed by a talk on October 25 by him on "Photosynthesis: Stories of the Past." Everyone enjoyed his animated talk-it was full of life and enjoyment. Here, I present a brief pictorial essay on Govindjee at his 80th (really 81st) birthday in Třeboň during October 23-25, 2013.
Keywords: United States; History, 21st Century; Česká republika; Photosynthesis; Spojené státy americké; botanika; History, 20th Century; Czech Republic; Botany; dějiny 21. století; fotosyntéza; dějiny 20. století